Lyapunov-Based Controller for a Class of Stochastic Chaotic Systems. (9th December 2014) - Shokouhi-Nejad, Hossein; Rikhtehgar Ghiasi, Amir; Pezeshki, Saeed
Abstract : This study presents a general control law based on Lyapunov's direct method for a group of well-known stochastic chaotic systems. Since real chaotic systems have undesired random-like behaviors which have also been deteriorated by environmental noise, chaotic systems are modeled by exciting a deterministic chaotic system with a white noise obtained from derivative of Wiener process which eventually generates an Ito differential equation. Proposed controller not only can asymptotically stabilize these systems in mean-square sense against their undesired intrinsic properties, but also exhibits good transient response. Simulation results highlight effectiveness and feasibility of proposed controller in outperforming stochastic chaotic systems.